Pembuatan Hair Tonic Dengan Memanfaatkan Air Limbah Cucian Beras Putih - Pangastuti, Fang; Tritanti, Asi (Universitas Negeri Jakarta, 2023)
Making hair tonic products aims to process white rice washing waste water into a hair tonic product, get the right formula for making hair tonic products by utilizing white rice washing waste water, and find out people's interest in the product. The method used is the 4D development method, namely define (definition) including analysis of utilization and needs as well as literature studies related to rice washing waste water and hair tonic then determine the reference product, design (planning) including making 3 formulas into hair tonic products along with packaging, develop (development) includes product validation tests, dissemination (distribution) includes liking tests and pH tests. The results obtained were the processing of white rice washing wastewater into hair tonic products by sterilizing at a temperature of 121℃ for 17 minutes, obtaining the right formula, and liking test results with a percentage value of 88.75%. Based on the assessment scale for Akdon modification products, it shows that the products are well received by the public.